2021
DOI: 10.1177/26338076211014590
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and punishment: A global paradox?

Abstract: Across the world, the most marginalised groups of society are overrepresented in prisons and institutions of the criminal justice system. Besides racial and ethnic minorities, prisons worldwide disproportionately house individuals who count among the least educated, most unemployed and poorest groups of society. However, it is one of the paradoxes of penality that whilst it is obvious that criminal justice systems across the world target disadvantaged populations, the link between imprisonment and socio-econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Individual‐level studies consistently show that immigrant involvement in crime is similar to or lower than that of native‐born citizens (e.g., Lee et al, 2001; Sampson et al, 2005). However, researchers have found that socially marginalized groups are overrepresented in the criminal justice system, including prisons (see e.g., Karstedt, 2021). Anderson (2022, p.1) argues that overrepresentation of ethnic and racial groups in prisons “suggests the possibility of widespread bias in law enforcement and/or a pattern of socioeconomic exclusion”.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individual‐level studies consistently show that immigrant involvement in crime is similar to or lower than that of native‐born citizens (e.g., Lee et al, 2001; Sampson et al, 2005). However, researchers have found that socially marginalized groups are overrepresented in the criminal justice system, including prisons (see e.g., Karstedt, 2021). Anderson (2022, p.1) argues that overrepresentation of ethnic and racial groups in prisons “suggests the possibility of widespread bias in law enforcement and/or a pattern of socioeconomic exclusion”.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Study of the United States—and its uniquely punitive features—has tended to dominate the discussion of prison disproportionalities, yet prior research shows comparable extents of disproportion occurring in several countries and under varied punitive conditions (Tonry 1997). Indeed, it is now practically a criminological truism that “everywhere, the most marginalized groups of society are overrepresented in prisons” (Karstedt 2021, 5). However, cross-national research observing and measuring this overrepresentation remains scarce.…”
Section: Introductionmentioning
confidence: 99%